2020
DOI: 10.1159/000508419
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Pneumatic and Ho:YAG Laser Lithotripsy in the Management of Lower Ureteric Stones

Abstract: Introduction: Besides extracorporeal shockwave lithotripsy, semi-rigid ureteroscopy (URS) has become an equal therapy of choice for the treatment of most distal ureteric stones. Before the wide availability of laser lithotripsy as a tool for stone fragmentation, pneumatic lithotripsy was, and still is, widely used. In a country like Iraq, availability and affordability are the huge questions asked. Besides the capital investment for a laser machine, the pneumatic device is reusable, whereas the laser fibers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Generally, ordinary images have a relatively large dynamic range, and the gray values of pixels are evenly distributed in the entire gray range. Therefore, intuitively, the entire image will have a relatively high contrast, and the details can be seen very clearly [ 17 , 18 ]. The image demanipulation process is shown in Figure 3 .…”
Section: Laser Lithotripsy and Nursing Methodsmentioning
confidence: 99%
“…Generally, ordinary images have a relatively large dynamic range, and the gray values of pixels are evenly distributed in the entire gray range. Therefore, intuitively, the entire image will have a relatively high contrast, and the details can be seen very clearly [ 17 , 18 ]. The image demanipulation process is shown in Figure 3 .…”
Section: Laser Lithotripsy and Nursing Methodsmentioning
confidence: 99%
“…In our study, while 59.8% of the patients were applied JJ stents and 16.2% were applied external ureteral catheters, 24% did not have any stent. While the use of JJ stent was 86.2% in the study of Khoder et al [9], JJ stenting was routinely applied to all patients (100%) in a prospective study of 50 patients published in 2020 [35]. In our study, when the use of stent was compared between the two groups, it was seen that statistically fewer postoperative catheters were applied in patients who underwent LL than those who underwent PL (70.2% and 82.4%).…”
Section: Discussionmentioning
confidence: 50%
“…Rigid stones revise their position during the pneumatic lithoclast, the location changes during the procedure make it difficult for the urologist to emphasize on stone and break it. At the same time as affirmed in several pieces of research Ho: YAG Laser carries superior usefulness weigh against pneumatic modality with improved stone-free rates and decreased operative duration 14,20 . This study results indicated 86.7% versus 63.3% stone clearance on follow-up radiological investigations such as ultrasound KUB and X-rays KUB, in pneumatic and laser groups respectively.…”
Section: Resultsmentioning
confidence: 85%
“…This study results indicated 86.7% versus 63.3% stone clearance on follow-up radiological investigations such as ultrasound KUB and X-rays KUB, in pneumatic and laser groups respectively. Retropulsion had only been reported in proximal ureter calculi 20 .…”
Section: Resultsmentioning
confidence: 99%